A phase 3b study of sofosbuvir plus ribavirin in treatment‐naive and treatment‐experienced Korean patients chronically infected with genotype 2 hepatitis C virus. Issue 5 (10th February 2016) - Ahn, S. H.; Lim, Y. S.; Lee, K. S.; Paik, S. W.; Lee, Y. J.; Jeong, S. H.; Kim, J. H.; Yoon, S. K.; Yim, H. J.; Tak, W. Y.; Han, S. Y.; Yang, J. C.; et al.
Summary: In Korea, patients with chronic hepatitis C virus (HCV) infection are typically treated with pegylated interferon‐alpha plus ribavirin, but interferons are contraindicated in many patients and are often poorly tolerated, particularly by the elderly and those with advanced liver disease. No interferon‐free treatment regimens are approved in Korea. Sofosbuvir is an oral nucleotide analog inhibitor of the HCV nonstructural 5B RNA polymerase. It is approved in the USA, European Union and Japan for treating a number of HCV genotypes, including genotype 2. Genotype 2 has a seroprevalence of 38–46% in Korea. This single‐arm, phase 3b study (NCT02021643) examined the efficacy and safety of sofosbuvir plus ribavirin (12‐week duration) in chronic genotype 2 HCV‐infected treatment‐naive and treatment‐experienced Korean patients with and without cirrhosis. The proportion of patients with sustained virologic response 12 weeks after treatment discontinuation (SVR12) was 97% (125/129), with 96% (101/105) of treatment‐naive and 100% (24/24) of treatment‐experienced patients achieving SVR12. Two patients experienced virologic failure ( n = 1, on‐treatment failure; n = 1, relapse). No patient discontinued study treatment due to an adverse event (AE). The most common treatment‐emergent AEs were headache (18%, 23/129) and pruritus (15%, 19/129). Few patients had grade 3 AEs (5%, 6/129) or grade 3 laboratory abnormalities (12%, 15/129). No grade 4 AE was reported. These data suggest that 12 weeks of treatment with the all‐oral, interferon‐free regimen of sofosbuvir plus ribavirin is effective and well tolerated in Korean patients with chronic genotype 2 HCV infection.